Surgical treatment of septic subtendinous calcaneal bursitis in 2 cows - Kofler, Johann; Erlacher, Hannah; Pagliosa, Geane (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2019)
Two cows were referred to our clinic with moderate to severe hindlimb lameness due to infected wounds over the lateral and caudal aspect of tuber calcanei (TC) with regional swelling, consistent with septic subtendinous calcaneal bursitis. Ultrasonography (7.5 MHz linear probe) revealed fibrinous/fibrino-purulent inflammatory bursal effusions in both cows, complete rupture of the superficial digital flexor tendon and a small, circumscribed, irregular and rough bone contour of the TC in case 2. Radiography revealed physiological findings in case 1, whereas there were osteomyelitis and later bone sequestration in case 2. Treatment consisted of thorough wound debridement, establishing access to the bursa, removal of all exudate and fibrin, creation of additional drainage portals and meticulous lavage using sterile 0.9 % saline solution containing 0.1 % povidone-iodine performed under sedation and intravenous regional anesthesia. In case 2, the infected bone area of the TC was removed using a curette. However, a small bone sequestration developed from the TC 15 days later, which was associated with osteomyelitis. This was removed during a second surgical intervention. Systemic antimicrobial and anti-inflammatory medications were administered peri- and post-surgically and the bursae flushed repeatedly. The affected tarsi were covered with a modified Robert-Jones bandage or a fiberglass cast. Cows 1 and 2 were discharged from the clinic 25 and 27 days after initial surgery, respectively, displaying mild lameness. Both cows were alive, not lame and were in advanced stages of pregnancy at the time of manuscript submission 8 and 12 months later, respectively. This report describes in detail 2 severe cases of septic fibrino-purulent subtendinous calcaneal bursitis in cows that were successfully treated by surgical debridement and lavage under a practical anesthetic protocol, followed by proper wound management in the post-surgical period. These effective surgical procedures can be performed under field conditions given the availability of adequate equipment.
Keywords: Subtendinous calcaneal bursa; synovial sepsis; hock lesion; cattle